The value of surgical admissions for malignant uterine cancer. A comparative analysis of robotic, laparoscopic, and laparotomy surgery in a university hospital - Specchia, Maria Lucia; Arcuri, Giovanni; Di Pilla, Andrea; La Gatta, Emanuele; Osti, Tommaso; Limongelli, Prospero; Scambia, Giovanni; Bellantone, Rocco Domenico Alfonso (Frontiers in Public Health, 2022)
Background: Robotic surgery for malignant uterine cancer raises issue of economic sustainability for providers. The objective of this study was to assess the value of surgical admissions for malignant uterine cancer in a University Hospital through an analysis of their costs and outcomes by comparing three different surgical approaches (laparotomy, laparoscopic, and robotic surgery). Methods: Hospitalizations between 1 January 2019 and 31 October 2021 for malignant uterine cancer surgery were selected and stratified. For each surgical approach, mean values (with 95% confidence intervals, CI) were calculated for cost items. Moreover, 30-days readmission frequency was calculated for the three approaches compared to each other. We used ANOVA, Student's t-test, Relative Risk for statistical analysis. A break-even analysis was carried out by evaluating the volume of robotic and non-robotic surgical admissions. Results: 1336 hospitalizations were included in the study, 366 with robotic, 591 with laparoscopic, and 379 with laparotomy surgery. Robotic surgery compared to laparoscopic and laparotomy ones, showed a statistically significant difference (p<0,001) in economic margin, which was largely negative (-1069.18 €; 95%CI: -1240.44 – -897.92 €) mainly due to devices cost, and a lower percentage of 30-days readmissions (1.4%; 95%CI: 0.2% – 2.6%), with a statistically significant difference only versus laparotomy (p=0.029). Laparoscopic compared to laparotomy surgery showed a significantly (p<0,001) more profitable economic margin (1692.21 €; 95%CI: 1531.75 € – 1852.66 €) without a significant difference for 30-days readmissions. Break-even analysis showed that, on average, for each malignant uterine cancer elective surgery performed laparoscopically, 1.58 elective robotic surgeries are sustainable for the hospital (95% CI: 1.23 – 2.06). Conclusions: Break-even analysis could be a useful tool to support hospital management in planning and governance of malignant uterine cancer surgery. Systematic application of this tool will allow defining over time right distribution of robotic, laparoscopic and laparotomy surgeries’ volumes to perform to ensure both quality and economic-financial balance and therefore value of uterine oncological surgery. Concerning research, this study paves the way for a multicentric study, the extension of outcomes of malignant uterine surgery to be considered and assessed, and the future inclusion of other therapeutic interventions in the analysis